Triterpenoid wax esters confirm Ficus religiosa in archaeological sequences within the Mayadevi temple shrine, Lumbini – the birthplace of Buddha - Reay, Michaela K.; Simpson, Ian A.; Zhao, Wanyue; Coningham, Robin A. E.; Davis, Christopher; Acharya, Kosh Prasad; Manuel, Mark; Strickland, Keir; Gilliland, Krista; Kinnaird, Tim C.; Bull, Ian D. (Frontiers in Geochemistry, 2025)
Leaf wax biomarkers permit chemotaxonomic identification of past vegetation in archaeological contexts. At the birthplace of Buddha, Lumbini in Nepal, archaeological evidence of a multi-phase tree shrine from the earliest beginnings of Buddhism has been uncovered in archaeological sequences within the Mayadevi Temple. As yet there has been no scientific attempt to establish the species of tree(s) occupying the “central open space” within the ancient shrine, or in the wider sacred landscape, despite this being an issue of significance for understanding early Buddhist practice. The cuticular leaf waxes of three tree species sacred and venerated in Buddhist tradition - Saraca asoca, F. religiosa and Shorea robusta were characterised, with additional identification achieved following hydrolysis of triterpenoid esters. Diagnostic distributions of triterpenoid esters were observed for F. religiosa leaves (β-amyrin, α-amyrin and lupeol esters with C16:0, C18:2, C18:1, C18:0, C20:2, C20:1, C20:0, and C22:0 fatty acids, Ψ-taraxasteryl eicosanoate, Ψ-taraxasterol behenate) and S. robusta leaves (taraxeryl linoleate). Chronologically controlled and contextualised analyses of archaeological soil lipids characterise the triterpenoid ester distribution within the main shrine’s “central open space”, an adjacent palaeo-channel, the monastic site and early village mound. The presence of β-amyrin palmitate and α-amyrin palmitate, with longer-chain homologues (β-amyrin stearate, α-amyrin stearate and β-amyrin eicosadienoate) in the soil indicate that the F. religiosa tree occupied the “central open space” throughout development of the tree shrine, alongside a F. religiosa grove close to the palaeo-channel adjacent to the Mayadevi Temple. Beyond these locations, F. religiosa occurred only rarely in the historic Lumbini landscape, although there are enhanced triterpenoid esters in a foundation pit in the village and in an occupation surface from the monastic site; there is no biomarker evidence of other trees. F. religiosa is a sacred tree species of long-standing in South Asia; our analysis indicates its transition into Buddhist religious culture and demonstrates that leaf-wax biomarkers can provide enhanced visibility to archaeological tree shrines in South Asia.